Increased Level of The Plasminogen Activator Inhibitor Type-1 is Associated with Severity of NAFLD - Didik Indiarso; Agung Prasetyo; Hirlan Hirlan; Hery Djagat Purnomo (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) has been the most common cause of chronic liver disease worldwide. In NAFLD, elevated Plasminogen Activator Inhibitor-1 (PAI-1) is associated with risk factors for thrombosis and hypercoagulable state.Objective: This study explored the relationship between NAFLD as an independent factor for increasing PAI-1 in the presence of metabolic syndrome and insulin resistance.Methods: This observational study used a cross-sectional design with 80 subjects including 40 patients with NAFLD and 40 without NAFLD at dr. Kariadi Semarang who met the inclusion and exclusion criteria. Measurement of plasma PAI-1 levels was done using ELISA method.Results: A total of 80 patients were included. In the case group, based on abdominal ultrasound, NAFLD was mostly found in the mild category (86%), while the rest were moderate (10%), and severe (4%). Only 25% were found in the Simple Steatosis category, and 75% were suspected of having NASH (NAS = 3-4) and NASH (NAS > 5). There was a significant difference between plasma PAI-1 level and the incidence of NAFLD (p = 0.011). The mean PAI-1 level between the three NAFLD severity categories also shown a significant difference (p = 0.032).Conclusion: There is an increase in PAI-1 levels in patients with NAFLD. PAI-1 levels have an independent effect on the degree of liver fibrosis in patients with NAFLD.